2022
DOI: 10.1038/s41598-022-21849-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative albumin and white blood cell count in surgical site infections following whipple surgery

Abstract: Whipple surgery is associated with a high risk of surgical sites infections (SSIs). Nutritional deficiency has been associated with an increased risk of wound infections. This study aims at exploring the role of preoperative albumin levels in predicting the risk of SSIs following Whipple surgery. A total of 23,808 individuals were identified from the ACS-NSQIP database from years 2011 to 2017. The primary exposure was pre-operative albumin while the secondary exposure was white blood cell (WBC) count. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In the present study, multivariable logistic regression analysis for abdominal surgery revealed that age, chronic liver disease, bowel preparation, colon surgery, pancreatic surgery, preoperative albumin level, surgical wound class, surgical approach, and colostomy/ileostomy at the end of surgery were associated with SSI following abdominal surgery. The roles of age, colon surgery, pancreatic surgery, preoperative albumin level, surgical wound class, surgical approach, and stoma in SSI are well known 17–19 . Moreover, there was an increased risk of SSI in patients with chronic liver disease after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, multivariable logistic regression analysis for abdominal surgery revealed that age, chronic liver disease, bowel preparation, colon surgery, pancreatic surgery, preoperative albumin level, surgical wound class, surgical approach, and colostomy/ileostomy at the end of surgery were associated with SSI following abdominal surgery. The roles of age, colon surgery, pancreatic surgery, preoperative albumin level, surgical wound class, surgical approach, and stoma in SSI are well known 17–19 . Moreover, there was an increased risk of SSI in patients with chronic liver disease after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of age, colon surgery, pancreatic surgery, preoperative albumin level, surgical wound class, surgical approach, and stoma in SSI are well known. [17][18][19] Moreover, there was an increased risk of SSI in patients with chronic liver disease after abdominal surgery. In the present study, chronic hepatic dysfunction included abnormal liver enzyme concentrations, hepatocellular carcinoma, cirrhosis, and hepatitis.…”
Section: Latent Class Analysismentioning
confidence: 99%
“…6,11 In addition, leukocytosis was found to be a predictor for the development of SSI, which aligns with previous research. 31 Additionally, prolonged operation duration was recognized as an independent factor for SSI development in other studies, as it increases the risk of infection due to extensive surgical procedures and incisions, prolonged anesthesia, blood loss, and weaning antimicrobial prophylaxis concentration. 6,32 Furthermore, administering antibiotics one hour before operation has been reported as a predictor for SSI in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All methods were carried out in accordance with the World Medical Association Declaration of Helsinki 19 . Institutional research ethics board review and informed patient consent were not required as the data came from a large, deidentified registry, which is an accepted practice for studies based on ACS NSQIP data 20 .…”
Section: Methodsmentioning
confidence: 99%